Kolaviron and Garcinia kola Seed Extract Protect Against Ischaemia/Reperfusion Injury on Isolated Rat Heart - Oyagbemi, Ademola Adetokunbo; Bester, Dirk; Esterhuyse, Johan; Farombi, Ebenezer Olatunde (Drug Research, 2018)
Background The incidence of cardiovascular diseases and its associated complications have increased greatly in the past three decades. The purpose of this study was to evaluate the acute cardioprotective effects of Garcinia kola (GK) seed extract and Kolaviron (KV) and determine mechanisms of action involving RISK signalling pathways.Methods Male Wistar rats were used in this study. Hearts were excised and mounted on the Langendorff perfusion system. The control, group 1 was perfused with dimethyl sulfoxide (DMSO), group II with KV and group III with GK respectively. Western blot analyses were performed on frozen heart tissues.Results Isolated rat hearts perfused with KV and GK attenuated apoptotic pathways with significant reduction in p38 MAPK protein phosphorylation, as well as reduction in total caspase 3, cleaved caspase 3 (Asp 175) and PARP cleavage. KV and GK also down-regulated p-JNK1 (Tyr 185) and p-JNK 2 (Thr 183) protein expression at the 10 min reperfusion time ponit. Cardioprotection was achieved in part, by enhancement of the reperfusion injury signalling kinase (RISK) pathway; as evidenced by significant increases in protein expresion of Akt/PKB and p-Akt/PKB (Ser 473) in KV and GK respectively.Conclusions KV and GK supplementation led to significant increases in the expressions of survival proteins. It is noteworthy that both KV and GK supplementation offered cardioprotection in ischaemic/reperfusion injury rat heart model. In all, GK showed better cardioprotective effect that KV.
Keywords: Kolaviron (KV); Garcinia kola (GK) seed extract; antioxidant; reperfusion injury; cardio-protection